Working With People (WWP) in Rural Development Projects: a Proposal from Social Learning - Cazorla, Adolfo (Pontificia Universidad Javeriana, 2013)
This paper shows a conceptual framework which synthesizes the evolution of the “modern project” and its dominant values, reaching to a new approach for the planning of rural development projects in the post-modernity: Working With People (WWP). The WWP model proposed is integrated into international discussions of “social learning” and it incorporates key elements of planning as social learning, collaborative participation theory and project management models. WWP is the result of 25 years of experience from the research group GESPLAN in several European contexts and emerging countries. The WWP implementation has led to different methodologies and applied research. This new way of thinking opens up new fields of research in rural development projects planning, evaluation and management.